Pengaruh etika Kerja dan Komitmen pada Organisasi terhadap Kepuasan Kerja - Mochammad Maksum; Wahyu Purwanto; G. S. Chotidjah (agriTECH, 2006)
Work ethic have strategic role beyond company because its have many implication. One of theories which explain about work ethic is Webers Theory. Webers Theory tries to make a connection between success in business world and religious belief Weber 's Theory can be applied into various religious beliefs and do not focus only in one belief. Unfortunately, most researches about work ethic tend to using work ethic in Protestant Work Ethic framework, this framework may be fit to use in western countries. There is little research which tries to scrutinize Islamic work ethic. On the contrary, in eastern countries such as Indonesia which Islam was became major religion of its citizens, Islamic Work Ethic concept was more appropriate to used rather than Protestant Work Ethic. This research studied the impact of lslamic Works Ethic and organizational commitment toward job satisfaction and life satisfaction of PT BPR SKA Divisi Agrodana employees. Population in this research is 72 employees of PT BPR SKA Divisi Agrodana employees. All populations member were became respondent in this research. Questionnaire method used in this research to collect the data. Structural Equation Modeling was used as data analysis technique. To simplify its computation, AMOS 4.01 computer program were used. The result show that Islamic Work Ethic and organizational commitment have positive and significant impact toward job satisfaction, further more job satisfaction have positive and significant impact toward life satisfaction. Model proposed in this study was met the goodness of fit criterions, thus this model were fit both theoretically and empirically.